2021
DOI: 10.1007/s11419-020-00565-4
|View full text |Cite
|
Sign up to set email alerts
|

A fluorine turns a medicinal benzodiazepine into NPS: the case of flualprazolam

Abstract: Purpose The purpose of this review is to summarize the existing knowledge on flualprazolam, a novel ‘designer’ benzodiazepine that derives from the fluorination of the phenyl moiety in the ortho-position of alprazolam. Methods An extensive literature search was carried out in PubMed, Google Scholar and World Wide Web using relevant keywords. All articles found were gathered, and the available information is presented. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Flualprazolam is a fluorinated analogue of alprazolam, but there is little information in the literature regarding its specific pharmacological effects because it was never legitimately marketed. Based on its structural similarity to traditional benzodiazepines, alprazolam and triazolam, and user reports, flualprazolam most likely has similar CNS depressant effects ( 189 , 190 ). Flualprazolam was reported to be in circulation by the EMCDDA and DEA in 2018; as of the third quarter in 2020, flualprazolam was the most reported novel benzodiazepine in the USA.…”
Section: Nps Benzodiazepinesmentioning
confidence: 99%
“…Flualprazolam is a fluorinated analogue of alprazolam, but there is little information in the literature regarding its specific pharmacological effects because it was never legitimately marketed. Based on its structural similarity to traditional benzodiazepines, alprazolam and triazolam, and user reports, flualprazolam most likely has similar CNS depressant effects ( 189 , 190 ). Flualprazolam was reported to be in circulation by the EMCDDA and DEA in 2018; as of the third quarter in 2020, flualprazolam was the most reported novel benzodiazepine in the USA.…”
Section: Nps Benzodiazepinesmentioning
confidence: 99%
“…An analysis of user reports has indicated that fluclotizolam is reported to be a potent benzodiazepine, with a dose of more than 0.75 mg reported as having a 'heavy effect' [47]. Flualprazolam has been reported in a number of DUID incidences, an 'anaesthesia robbery' case, as well as being detected post-mortem in a number of intoxications [48][49][50][51].…”
Section: Binding Affinitymentioning
confidence: 99%
“…[11][12][13] It is also found in many hypnotics and psychiatric drugs. [14,15] The excess of it causes fluorosis and also responsible in disruption of immune system, acute gastric and kidney problems. [16,17] Besides industrial applications, cyanide is well known for its high toxicity as inhalation or consumption can cause health concern or even fatality.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride is often added to drinking water and toothpaste to maintain dental health and treatment of osteoporosis [11–13] . It is also found in many hypnotics and psychiatric drugs [14,15] . The excess of it causes fluorosis and also responsible in disruption of immune system, acute gastric and kidney problems [16,17] .…”
Section: Introductionmentioning
confidence: 99%